Mobility disorders and pain, interrelations that need new research concepts and advanced clinical commitments - Sascha Sajer (PAGEPress Publications, 2017)
This Perspective will discuss topics recently suggested by Prof. Helmut Kern, Vienna, Austria, to advance the research activities of his team, that is: Topic A, 10 years post RISE; Topic B, New research for new solutions on old research questions; Topic C, Working groups on nerve regeneration, training-parameters of seniors in different ages, muscle adaptation; and studies of connective tissue and cartilage. This Perspective summarizes some of the basic concepts and of the evidence-based tools for developing further translational research activities. Clinically relevant results will ask for continuous interests of Basic and Applied Myologists and for the support during the next five to ten years of public and private granting agencies. All together, they will end in protocols, devices and multidisciplinary managements for persons suffering with muscle denervation, neuromuscular-related or non-related pain and for the increasing population of old, older and oldest senior citizens in Europe and beyond.